DOES BOSNIAN LEAGUE BASKETBALL HAVE A TENDENCY OF QUALITY IMPROVEMENT? - Vlatko Šeparović; Edin Užičanin; Haris Pojskić (Sport Scientific And Practical Aspects, 2025)
This work is based on 13 standard indicators of situational effectiveness in basketball and its aim is to get the answer to the question whether Bosnian League basketball has a tendency of quality improvement. Two seasons of League 6, basketball championship in Bosnia and Herzegovina, 2004/2005 & 2009/2010, were used to get the data for this research. Thirty (30) games were played in each of the two seasons. T-test was used to determine the significance of arithmetic means between winning and losing sides in applied situational indicators, and discriminative analysis was used to determine the difference on a global level as well as contribution of each situational indicator to discriminant function. Research results confirm that the quality of Bosnian League basketball in the 2009/2010 playoff games is equally dispersive on a balanced level for almost every team (6), so in comparison to the 2004/2005 season, it can be said that Bosnian League basketball has reached considerably higher level of quality. Balanced quality of teams in Bosnian League 6 in the 2009/2010 season causes high quality defense, and such defense on the other hand creates versatility and new quality on the offensive end, so now three-point field goal made and blocked shot appear as new indicators which create difference between winners and losers. It can be expected that in the near future some other team will by its quality pull away from the other teams, and create a new and positive tendency of basketball development in Bosnia and Herzegovina.